Pure NOTES transvesical venous ligation: translational animal model of varicocelectomy - Osório, L (2012)
OBJECTIVE: To assess the feasibility of pure natural orifice transluminal endoscopic surgery (NOTES) transvesical venous ligation mimicking bilateral varicocelectomy in an animal model. MATERIALS AND METHODS: Transvesical NOTES bilateral venous ligation was performed in 6 female pigs by considering lower epigastric vessels as a model for gonadal vessels. Under flexible cystoscopic guidance, a cystotomy was created on the anterior bladder. The flexible cystoscope was introduced through the over tube, and the lower epigastric vessels were visualized in retroflexion. Thulium laser was used to cut and coagulate the vessels. A bladder catheter was left in place for 4 days in all animals and they were sacrificed 15 days after the procedure. RESULTS: The procedure was successfully carried out in all animals without intraoperative complications. Epigastric vessels were safely cut and coagulated using the thulium laser. Median time for the overall procedure, including establishment of the transvesical port, was 23 minutes (range 20-30). No complications were encountered during the postoperative follow-up period. Postmortem examination revealed complete coagulation and separation of vessels. CONCLUSION: An animal model mimicking a NOTES transvesical bilateral varicocelectomy procedure is successfully shown in the present study. Despite being encouraging, these novel findings need to be interpreted with caution. Further research is warranted and development of purpose-built instrumentation is awaited to define potential urological applications of transvesical NOTES